Adverse Event : Myocardial Injury after Non-Cardiac Surgery (MINS) Post Craniectomy in Critical Care - Fajri, Doni; Anggraeni, Novita; Hidayat, Nopian; Ananda, Pratama (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Intracerebral hemorrhage (ICH) describes the non-traumatic parenchymal hemorrhage caused by the rupture of cerebral vessels, accounting for 2030% of all strokes. ICH will cause compression on the surrounding brain tissues, eventually giving rise to increased intracranial pressure. Decompressive craniectomy (DC) effectively reduce intracranial pressure. Myocardial injury is defined as an elevation of cardiac troponin levels with or without associated ischemic symptoms. Case a male, 66 years old patient was admitted to the ICU after undergoing Emergency Craniectomy Hematoma Evacuation due to Spontaneous ICH. After 52 hours of treatment, the patient was found to have ventricular tachycardia (VT) on the monitor and restlessness. The patient was also found to have comorbid hypertension. On a 12-Lead ECG we found NSTEMI, and Troponin I level was measured at 453.0 ng/L (positive). This patient was treated with anticoagulants, antiplatelet and statin, with monitoring of the ECG daily. On The 6th day patient was moved to High Care Unit (HCU). Myocardial Injury after Noncardiac Surgery is defined by elevated postoperative cardiac troponin concentrations, with or without accompanying symptoms or signs. It typically occurs within 30 days after surgery. The management of MINS involves the use of anticoagulants and antiplatelet therapy. Anticoagulant therapy should be considered between benefit and risk of re-bleeding post operative. MINS is a rare condition but is associated with an increased risk of 30-day mortality. A multidisciplinary treatment approach and a coordinated team effort are essential for improving the outcomes of patients with this condition.